Ratiometric Nanosensor for Visual Detection of Copper Ions - Qi, Shengda; Ren, Cuiling; Chang, Yanping; Chen, Hongli; Chen, Yonglei; Chen, Xingguo; Xie, Yujie (Asian Journal of Chemistry, 2014)
In this paper, a new ratiometric fluorescent nanosensor was synthesized simply and economically and applied for Cu2+ detection in water samples. This nanosensor was a type of dual-emission quantum dots which was composed silica coated red CdTe quantum dots and glutathione modified green CdTe quantum dots. The probe exhibits a dynamic response range for Cu2+ from 6.7 × 10-8 to 8 × 10-7 mol L-1 with a detection limit of 2.5 × 10-8 mol L-1. Other alkali, alkaline earth and transitional metal ions including K+, Na+, Mg2+, Zn2+, Pb2+, Ni2+, Cr3+ and Fe3+ had no significant interferences on Cu2+ determination. Binding Cu2+ to the nanosensor make the colour of the solution change from green to orange under UV light irradiation, which illustrates that this new sensor can realize visually detection of Cu2+.